Mathematical Critical Thinking Ability: The Effect of Scramble Learning Model assisted by Prezi in Islamic School. (February 2020) - Yasin, Muhamad; Huda, Syamsul; Komarudin,; Suherman,; Septiana, Reni; Palupi, Endah Kinarya
Abstract: This study aims to determine the effect of scramble learning models assisted by prezi on mathematical critical thinking skills. The type of research used was quasi-experimental design. Data collection was performed by tests of mathematical critical thinking skills. Data were analysed using one-way ANOVA test and continued with multiple comparisons. Hypothesis testing used one way ANOVA with a significance level of 5%. The result of hypothesis test showed F count is 3.24 and F table is 3.10 or F count is greater than F table, then, hypothesis 0 is rejected. This study found that the average score of the class using scramble learning model assisted by prezi was higher than the class that used scramble learning model and conventional learning model. Based on these results it can be concluded that there is an influence of the scramble learning model assisted by prezi on the mathematical critical thinking ability of grade VII.